CHANGES IN CORTICOSTEROCYTES OF THE ZONA RETICULARIS AND СHROMAFFIN CELLS OF THE ADRENAL GLAND IN RATS DURING THE INHIBITION OF TESTOSTERONE SYNTHESIS - Skotarenko, T.A.; Shepitko, V.I.; Stetsuk, E.V.; Boruta, N.V. (World of Medicine and Biology, 2022)
Metabolic disorders, which are the main causes of many diseases and can be linked to the pathogenesis of other nosologies, remain relevant objects of scientific research. It has been proved that testosterone is an important biological regulator of metabolic processes in the male body. Modern studies are performed on the effect of testosterone deficiency on the state of neurons, testicles, liver and other body organs and tissues. The paper describes the main morphological changes of corticosterocytes of the reticular zone of the cortical substance and chromaffin cells of the medulla of the adrenal glands of white rats during central deprivation of testosterone synthesis through experimental blockade of gonadotropic hormones. It was established that inhibition of testosterone synthesis led to dystrophic changes and disruption of the synthetic function of corticosterocytes of the reticular zone, which was manifested at the microscopic level by the variability of morphometric indicators.
Keywords: testosterone deprivation; corticosterocyte reaction; reticular zone; cortical substance; medulla; adrenal gland